Eight further individuals with intellectual disability and epilepsy carrying bi-allelic CNTNAP2 aberrations allow delineation of the mutational and phenotypic spectrum. Issue 12 (20th July 2016) - Smogavec, Mateja; Cleall, Alison; Hoyer, Juliane; Lederer, Damien; Nassogne, Marie-Cécile; Palmer, Elizabeth E; Deprez, Marie; Benoit, Valérie; Maystadt, Isabelle; Noakes, Charlotte; Leal, Alejandro; Shaw, Marie; et al.
Abstract : Background: Heterozygous copy number variants (CNVs) or sequence variants in the contactin-associated protein 2 gene CNTNAP2 have been discussed as risk factors for a wide spectrum of neurodevelopmental and neuropsychiatric disorders. Bi-allelic aberrations in this gene are causative for an autosomal-recessive disorder with epilepsy, severe intellectual disability (ID) and cortical dysplasia (CDFES). As the number of reported individuals is still limited, we aimed at a further characterisation of the full mutational and clinical spectrum. Methods: Targeted sequencing, chromosomal microarray analysis or multigene panel sequencing was performed in individuals with severe ID and epilepsy. Results: We identified homozygous mutations, compound heterozygous CNVs or CNVs and mutations in CNTNAP2 in eight individuals from six unrelated families. All aberrations were inherited from healthy, heterozygous parents and are predicted to be deleterious for protein function. Epilepsy occurred in all affected individuals with onset in the first 3.5 years of life. Further common aspects were ID (severe in 6/8), regression of speech development (5/8) and behavioural anomalies (7/8). Interestingly, cognitive impairment in one of two affected brothers was, in comparison, relatively mild with good speech and simple writing abilities. Cortical dysplasia that was previously reported in CDFES was not present in MRIs of six individuals and only suspected in one. Conclusions: By identifying novel homozygous or compound heterozygous, deleterious CNVs and mutations in eight individuals from six unrelated families with moderate-to-severe ID, early onset epilepsy and behavioural anomalies, we considerably broaden the mutational and clinical spectrum associated with bi-allelic aberrations in CNTNAP2 .